Socio-cultural Challenges Faced by People with Physical Disabilities - Sharma, Anjana (Shahid Kirti Multidisciplinary Journal, 2024)
This qualitative study explores the challenges and the problems faced by people with physical disabilities in Nepal's cultural and social systems. In-depth interviews were conducted with eighteen participants living with physical disabilities in Kathmandu. Findings reveal significant challenges arising from exclusive social traditions, discrimination based on physical impairments, inaccessible infrastructure, and prejudiced social practices. These challenges hinder educational and employment opportunities, exacerbating vulnerability and exclusion from the mainstream socio-cultural system. The study also highlights limitations in government policies and programs, with poor implementation and cumbersome procedures leading to inadequate benefits for people with disabilities. Prejudiced social practices, discrimination, and inaccessible infrastructure further impede day-to-day activities, education, and employment, deepening vulnerability and marginalization. Institutional barriers within Nepali socio-cultural practices perpetuate the labeling of individuals with disabilities as incompetent and deficient, marginalizing their inclusion in social and cultural systems. Addressing these challenges requires comprehensive interventions promoting inclusivity and accessibility.